Customer service and service quality and its connection to entrepreneurs - Kamaruddin, Kardina; Ali, Noor Malinjasari; Borhanuddin, Rahayu Izwani; Mokhlas, Hasmi (Universiti Teknologi MARA, Terengganu, 2022)
When we talk about business and entrepreneurship, we also need to know about customer satisfaction and the service that it provided to customer. The reason is because when the customers are satisfied, they will become loyal customers and ensuring the business will have continuous profit. What is customer satisfaction?